IL-6 signaling is required for the development and regeneration of ear cartilage in microtia - Luan, Wenkang; Fan, Shujun; Jiang, Hanyi; Jiang, Dongwen; Yang, Jinxiu; He, Leren (Frontiers in Cell and Developmental Biology, 2025)
IntroductionCongenital microtia is a birth defect characterized by auricular underdevelopment, with unclear pathogenesis and unidentified pathogenic genes.MethodsDifferential expression analysis, weighted co-expression network analysis (WGCNA), protein-protein interaction (PPI) networks and support vector machine recursive feature elimination (SVM-RFE) identified the key biomolecules in microtia. Single-cell and intercellular communication analysis were used to decipher the key intercellular signaling pathway. We extracted primary cells and conducted Immuno precipitation mass spectrometry (IP-MS), co-Immuno precipitation (Co-IP) and RNA-sequencing (RNA-seq) to confirmed the mechanism. The intercellular communication network was confirmed through the cell co-culture system. Organoid and animal models further validated the role of key biomolecules.ResultsWe found that IL-6 may be the key biomolecule in microtia. Normal ear cartilage tissue is mainly composed of chondrocytes, but microtia auricular ear tissue contained chondrocytes and stem cells. IL-6 signaling pathway is the main intercellular communication pathways in microtia. We extracted primary chondrocytes and stem cells, and proved that IL-6 promotes the growth and migration of primary cells. The binding of IL-6 and IL-6R and Glycoprotein 130 (GP130) and the activation of their downstream were confirmed. Furthermore, IL-6 signaling pathway was proved to involve in the intercellular communication of microtia. Cartilage microspheres demonstrated the role of IL-6 in regeneration of ear cartilage. The preventive intervention of adeno-associated virus (AAV) on pregnant mice confirmed the role of IL-6 in vivo.ConclusionIL-6 signaling is the key biomolecule in the development and regeneration of auricular cartilage in microtia. IL-6 is a potential biomarker and preventive and therapeutic target for microtia patients.